A property of the β-Cauchy-type integral with continuous density
The aim of this paper is to extend a theorem from classical complex analysis proved by Davydov in 1949 to the theory of solutions of a special case of the Beltrami equation in the z-complex plane (i.e., null solutions of the differential operator _z - β zz _z,0 ≤ β < 1). We prove that if γ is a rectifiable Jordan closed curve and f is a continuous complex-valued function on γ such that the integral _γ{ζ γ: |ζ-t|≤ r |f(ζ) - f(t)||ζ - t|t/ζ|^θ | |n(ζ) - β ζζ n(ζ) |ds, θ = 2β1-β, converges uniformly on γ as r → 0, where n(ζ) is the exterior unit normal vector on γ at a point n(ζ) and ds is the arc length differential, then the β-Cauchy type integral 12(1 - β)π_γf(ζ)ζ - z|z/ζ|^ θ (n(ζ) - β ζζ n(ζ) )ds,z γ, admits a continuous extension to γ and a version of the Sokhotski - Plemelj formulae holds. Метою цієї статті є узагальнення теореми із класичного комплексного аналізу, що була доведена Давидовим у 1949 р., для теорії розв’язків окремого випадку рівняння Вельтрамі у z-комплексній площині (тобто нульових розв’язків диференціального оператора _z - β zz _z,0 ≤ β < 1)., number=11, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Abreu, Blaya R. and Bory, Reyes J., year=2008, month=Nov., pages=1443–1448